-26=-6w+2(w-3)

Simple and best practice solution for -26=-6w+2(w-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -26=-6w+2(w-3) equation:



-26=-6w+2(w-3)
We move all terms to the left:
-26-(-6w+2(w-3))=0
We calculate terms in parentheses: -(-6w+2(w-3)), so:
-6w+2(w-3)
We multiply parentheses
-6w+2w-6
We add all the numbers together, and all the variables
-4w-6
Back to the equation:
-(-4w-6)
We get rid of parentheses
4w+6-26=0
We add all the numbers together, and all the variables
4w-20=0
We move all terms containing w to the left, all other terms to the right
4w=20
w=20/4
w=5

See similar equations:

| 15+3x=x-7 | | 2(8j+6)=-2(-7j-8) | | 190=2x+30 | | F(x)=2(5x+6) | | 5x^2+16=-3 | | 4z+105=11z | | -(p-12)=5 | | 2x+2+4x=12+3x+11 | | 7b+39=10b | | 3(c+1)+6=6 | | 12a-1=11 | | 10.6y=2.1y-27.y | | 1.61x=14.973 | | 4(-w=+8) | | 6x-13+5=2x+11 | | -(f-8)+5=5 | | -7=6v-7v | | -7x^2+32=-80 | | 66+5x=11x | | -4(4a-4)=-112 | | 3n+15+5=55 | | 9x-3=18x-30 | | 15x-15(-2.5)=15 | | -2g=-2g-4(-g-5) | | 3^(x+5)=81 | | j/3−–3=4 | | -3+5(x+6)=30+7 | | 3(x=4)=33 | | 3/4y-10=20 | | 2=s−66/9 | | 0.42x=1.5708 | | 43a+26a=27 |

Equations solver categories